2022
DOI: 10.3390/en15072541
|View full text |Cite
|
Sign up to set email alerts
|

Hotspot-Aware Workload Scheduling and Server Placement for Heterogeneous Cloud Data Centers

Abstract: Data center servers located in thermal hotspot regions receive inlet air at a higher than theset temperature and thus generate comparatively high outlet temperature. Consequently, there is arise in energy that is consumed to cool down the servers that otherwise would undergo reliabilityhazards. The workload deployment across the servers should be resilient to thermal hotspots toensure smooth performance. In a heterogeneous data center environment, an equally importantfact is the placement of the servers in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The research mainly focuses on reducing energy use and improving the distribution of workloads while completing more tasks at high performance; they established lower criteria utilizing the data canter’s overall workload utilization and employed ant colony optimization to minimize the frequency of VMs movements. Research 14 explored optimization and ML-based work for load distribution in the cloud environment. The proposed model utilizes a bee colony optimization method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research mainly focuses on reducing energy use and improving the distribution of workloads while completing more tasks at high performance; they established lower criteria utilizing the data canter’s overall workload utilization and employed ant colony optimization to minimize the frequency of VMs movements. Research 14 explored optimization and ML-based work for load distribution in the cloud environment. The proposed model utilizes a bee colony optimization method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For more granular workload placement, i.e., server deployment, some researchers proposed hot-aware server placement approaches oriented to reduce the outlet temperature of servers to save cooling energy [24,25] . As for the research on power resource optimization using temporal differences in workload power consumption patterns, Hsu et al [26] proposed SmoothOperator, which uses the k-means to cluster service instances or servers with periodic synchronous power consumption patterns , and uses heuristics for optimal placement to reduce the sum of peaks in power supply nodes.…”
Section: Initial Value Of Pheromone Cmentioning
confidence: 99%
“…In 2022, M. Hasan Jamal et al [6] suggested a HAWDA and HASRA depending on thermal profiling considering outlet temperature detection. In order to reduce the peak output temperatures, HAWDA distributed workload on servers in a thermally efficient manner, while HASRA optimized server positioning in thermal hotspot areas.…”
Section: Related Workmentioning
confidence: 99%
“…The scheduling solution was optimized in terms of each metric specified in the QoS model using a QoS-driven CESS method [4]. It has been suggested to use an OP-MLB system, which combines a number of algorithms that cooperate to provide effective resource management for cloud environments [6] [7]. With more effective storage and V/F scaling improvement, the EARU model significantly reduces LLC disappointments and thus more effectively utilizes asset.…”
Section: Introductionmentioning
confidence: 99%